A study of the information-seeking behaviour of the researchers in the Parliamentary Research Unit at the Parliament of the Republic of South Africa - Swartz, Barbara Dawn (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.